2015
DOI: 10.1002/2015jg003009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of regional groundwater on carbon dioxide and methane emissions from a lowland rainforest stream in Costa Rica

Abstract: In the tropical rainforest at La Selva Biological Station in Costa Rica, regional bedrock groundwater high in dissolved carbon discharges into some streams and wetlands, with the potential for multiple cascading effects on ecosystem carbon pools and fluxes. We investigated carbon dioxide (CO 2 ) and methane (CH 4 ) degassing from two streams at La Selva: the Arboleda, where approximately one third of the streamflow is from regional groundwater, and the Taconazo, fed exclusively by local groundwater recharged w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 87 publications
1
22
0
Order By: Relevance
“…First, the effect of CO 2 evasion upon groundwater emergence likely resulted in enriched δ 13 C DIC values in the river relative to shallow groundwater, thereby causing a potential underestimation of the shallow groundwater contribution to the DIC flux in the mixing analysis. We would indeed expect large proportions of DIC being delivered to the Howard River via shallow flow paths, as p CO 2 within the shallow aquifer was >40,000 ppm on average (Rudge, ), and generally, the role of subsurface waters as carrier of biogenic C is increasingly recognised in the tropics (Duvert et al, ; Johnson et al, ; Oviedo‐Vargas et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the effect of CO 2 evasion upon groundwater emergence likely resulted in enriched δ 13 C DIC values in the river relative to shallow groundwater, thereby causing a potential underestimation of the shallow groundwater contribution to the DIC flux in the mixing analysis. We would indeed expect large proportions of DIC being delivered to the Howard River via shallow flow paths, as p CO 2 within the shallow aquifer was >40,000 ppm on average (Rudge, ), and generally, the role of subsurface waters as carrier of biogenic C is increasingly recognised in the tropics (Duvert et al, ; Johnson et al, ; Oviedo‐Vargas et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, where DIC originates from deeper groundwater, baseflow conditions can result in higher riverine DIC concentrations (Mann et al, ; Shih et al, ). Because different water flow paths can carry DIC of different origins (Oviedo‐Vargas et al, ), understanding the DIC export dynamics in rivers of the wet‐dry tropics requires an assessment of both water and DIC sources and pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater is known to be a source of CO 2 to surface waters, and other studies using natural tracers have shown that groundwater can be a major driver of surface water p CO 2 (Atkins et al, ; Maher et al, ; Sadat‐Noori et al, ; Oviedo‐Vargas et al, ). Over the annual cycle, positive significant linear relationships ( p < 0.001) were found between p CO 2 and 222 Rn (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Aquifers transporting high concentrations of dissolved C have been identified over the world [ Cruz and Amaral , ; Marrero et al , ; Evans et al , ; Kampman et al , ; Yamada et al , ; Genereux et al , ; Rivé et al , ; Kucharič et al , ]. It has been also shown that groundwater discharge from aquifers represents a significant source of atmospheric CO 2 to stream waters [ Crawford et al , ; Dinsmore et al , ; Oviedo‐Vargas et al , ] and coastal wetlands [ Cai et al , ; Atkins et al , ]. In this case, water composition of the Doñana aquifer has been found to be similar to that of precipitation water although more concentrated due to the effect of evapotranspiration in the soil, being also characterized by a slightly acid pH and with high concentrations of nitrates of agricultural origin [ Olías et al , ].…”
Section: Discussionmentioning
confidence: 99%